One glorious ambition : the compassionate crusade of Dorothea Dix - Kirkpatrick, Jane, 1946- (WaterBrook Press, 2013)
"In bringing nineteenth-century historical reformer Dorothea Dix to life, author Jane Kirkpatrick combines historical accuracy with the ... narrative of a woman who recognized suffering when others turned away, and the call she heeded to change the world"--P. [4] of cover.